Outcomes of root canal treatments with three different sealers for 120 fractured maxillary fourth premolar teeth in small-to medium-sized dogs - Kwon, Daehyun; Yoo, Dae Sung; Kang, Seong Soo; Jang, Kwangsik; Kim, Se Eun (Frontiers in Veterinary Science, 2024)
Tooth fracture is one of the most common traumatic maxillofacial injuries in dogs and cats. For fractures with pulp exposure occurring in functionally important teeth, the literature indicates that root canal treatment (RCT) is an effective therapy option that may be the remedy of choice before extraction. The most commonly reported fractures in the United States involve canine teeth; however, fractures of the maxillary fourth premolars are more common in Korea, where there are many smalland medium-sized dogs. RCT mechanically and chemically removes pulp tissue and bacteria (cleaning and shaping) from the infected root canal, and obturates the root canal with filling material to restore tooth functionality without inflammation. Various techniques, instruments, and materials used in humans have been modified for application in veterinary dentistry. This study analyzed the results of RCT of the maxillary fourth premolar in 120 small-and medium-sized dogs (weighing less than 25 kg) using three different sealers (silicone-based sealer, bioceramic sealer, and calcium hydroxide-based sealer) through a simple application of the single-cone technique. The overall success rate of RCT in maxillary fourth premolars was 90.83%, and there were no significant differences between the three different sealers. Furthermore, preexisting periapical lesion (PAL) was reconfirmed as a factor in reducing the success rate of RCT. In addition, the working length and master apical file of each root were analyzed in our study as a novel reference for endodontic veterinarians.